Antigenicity and immunogenicity of a synthetic peptide derived from a glucan-binding domain of mutans streptococcal glucosyltransferase. - Smith, D J (1993)
The immunogenicity and antigenicity of a multiply antigenic peptide construct containing four copies of the synthetic peptide TGAQTIKGQKLYFKANGQQVKG were measured in rodents and humans, respectively. The composition of this peptide construct (termed GLU) was derived from a major repeating sequence in the C-terminal region of mutans streptococcal glucosyltransferases that synthesize water-insoluble glucan (GTF-I). The GLU peptide elicited high levels of serum immunoglobulin G antibody to GLU after subcutaneous injection into Sprague-Dawley rats. These antisera also reacted with intact GTF isozymes from Streptococcus sobrinus and Streptococcus mutans (by enzyme-linked immunosorbent assay [ELISA] and Western blot [immunoblot] analyses) and with an 87-kDa glucan-binding protein from S. sobrinus (by Western blot). The synthesis of filter-retained glucan by GTF-Sd of S. sobrinus could be inhibited (30%) by preincubation with anti-GLU rat serum. Splenic and lymph node lymphocytes from rats injected once with S. sobrinus GTF isozymes demonstrated significant proliferation after 5 days of culture with GLU. The GLU peptide reacted with 4 of 29 human parotid saliva samples and 5 of 29 human serum samples (by ELISA). These results suggest that the GLU peptide contains B- and T-cell epitopes that are similar to those of intact mutans streptococcal GTFs and possibly certain other glucan-binding proteins as well. Furthermore, since antibody to this epitope(s) appears to inhibit GTF function, sequences within this peptide construct may have value for inclusion in a synthetic dental caries vaccine.